Impact of volatiles of the rhizobacteria Serratia odorifera on the moss Physcomitrella patens - Kai, Marco (Plant Signal Behav, 2010)
Volatiles are important infochemicals acting aboveground as well as belowground between organisms. In order to understand the complex volatile network of an entire ecosystem also the habitat at the border between the atmosphere and the soil has to be considered. Mosses are the dominant colonists of this habitat. Here we tested the reaction of the moss Physcomitrella patens upon exposure to rhizobacterial volatiles. In a closed test system, when CO(2) is a dominant component of the bacterial volatile mixture, P. patens growth was promoted, while in the natural-like open test system volatiles with negative influences possess their effects resulting in growth inhibitions of the moss. Growth retardation is less pronounced when the volatiles were applied in a later stage of development of the moss.